Status of Programmed Death Ligand 1 (PD-L1) by Immunohistochemistry and Scoring Algorithms - Giunchi, Francesca; Gevaert, Thomas; Scarpelli, Marina; Fiorentino, Michelangelo (Current drug targets, 2020)
The detection of the Programmed Death Ligand 1 (PD-L1) protein by immunohistochemistry is currently the only approved test predictive of response to drugs targeting the PD1/PDL1 axis. The role of this test is debated since several reagents have been used as companion diagnostics for different drugs on diverse immunostaining platforms. In addition, different scoring systems for PD-L1 immunohistochemistry have been applied in the registration studies regarding single drugs. This review deals with the various issues that are related to the immunohistochemical test for PD-L1. We discuss currently unsolved problems such as the advantages and the flaws of PD-L1 immunohistochemistry; the choice of the best reagents and the best scoring system. Finally, we review the current experiences on the role of immunohistochemistry for PD-L1 in clinical trials with immune checkpoint inhibitors.